DIMENSI PARTISI GRAF LENGKAP - Ramdhani, Vivi (IAIN Batusangkar, 2019)
Resolving partition is part of graph theory. Resolving partition is needed to obtain partition dimension. So far it has not been discussed regarding resolving partition of complete graphs. For this reason, this article explains the resolving partition of a complete graph.Given a connected graph and is a subset of write . Suppose there is then the distance between to is denoted in the form of . Then, suppose there is a partitioned set of , write , then we can obtain a representation of in the form of The partition set is called a resolving partition if the representation of each ? with is different. The minimum cardinality of the resolving -partition against is called the partition dimension of , denoted by pd (). To get the partition dimension of a complete graph, first we find the resolving partition og the graph, resolving partition orde After that, to assist in obtaining the partition dimensions of complete graph, we explained that if is is a connected graph then Based on these steps, finally obtained that the partition dimension of the complete graph, namely